Análise textural e geoquímica dos sedimentos do talude Continental do Oeste do Ceará. - Lima Neto, Inácio Ocinaí de (2017)
This research was carried out on the continental slope of the Acaraú region, 80 km from the coast, with depths between 60 and 2550 m. Its main objective was the sedimentary and geochemical characterization of the slope through the SIS100, SIS103, SIS105, SIS 400 and SIS108, as well as the texture, color, chemical and mineralogical composition, in order to assist in sediment classification of submerged zones. The studies were based on bibliographic references and methodologies were used for the description of seabed samples, by means of granulometric analysis, geochemistry by Dispersive Energy Spectroscopy, Fluorescence and X-Ray Diffraction. The geology of the continental slope is part of the passive margin, its evolution occurred in the period of rift of the ocean basin, being modeled by the tectonic action, the variations of the average level of the sea, the fluvial deposition, ocean currents, waves, between others. Considering the variety of colorations, we have uniformity between the first three samples (in the first 8 cm) showing yellowish gray color even distant and with different depths can be inferred in a single sedimentation event for these three, in relation to the second portion of the testimony SIS 105, and in SIS 460 and SIS 108, because they present different colors both in the same testimony and in the others, thus, it is considered distinct events characteristic for each of the colors found by the fact that there is no continuation in the other testimonies. With respect to the triangular diagram, the SIS 100, SIS 103 and SIS 460, presented similarity to the classification of sandy mud and low values of gravel, and classified as silt clay both levels of the SIS 105 sample and SIS 108 in the whole. After the study on the CaCO3 content of these, the first four presented values above 91%, the SIS 108 being the most distinct of these, presenting a maximum content of 10%. The mineralogy found with the aid of X-ray diffraction was: wollastonite, aragonite, calcite, quartz, goethite, illite-montmorillonite, muscovite, margarite and rutile. From the data obtained in the Scanning Electron Microscope, different minerals were observed on the surface of the gypsum, being the native copper of reducing environment, the detrital monazite, the pyrite formed in a reducing marine environment, and the detrital rutile. The results generated a greater base in the studies on the deep sea and its dynamics.